﻿Quality control standardization of Indonesian noni fruit (Morinda citrifolia) extract and evaluation of their angiotensin-converting enzyme inhibitory activity - Rizna Triana Dewi; Gian Primahana; Abdi Wira Septama; Marrisa Angelina; Lia Meilawati; Sofa Fajriah; Greesty F. Swandiny (Pensoft Publishers, 2022)
Morinda citrifolia fruit (Noni) has been used as a folk medicine in several countries. Noni possessed various pharmacological activities such as; anticancer, antidiabetic, antihypertensive, antarthritic, and antioxidants. The present study evaluated pharmacognostic properties, profiling of active constituent through High-Performance Thin Layer Chromatography (HPTLC) and Liquid Chromatography-High Resolution Mass Spectrometer (LC-HRMS) run for quantitative and qualitative phytochemical analysis and determining angiotensin-converting enzyme (ACE) inhibitor activity of Noni from three different locations. The physicochemical parameters of crude drugs and extracts met the requirement of Indonesian Herbal Pharmacopeia. Total phenol content was 2.16-3.08 mg GAE/g extract and total flavonoid content was 0.11 - 1.58 mg QE/g extract. HPTLC analysis revealed that scopoletin content in Noni was in the range of 0.44 - 0.51%. The results were also corresponding well with LC-HRMS fingerprint analysis. In addition, Noni fruit extract from Bogor potential exhibited activity in inhibiting ACE with an IC50 value of 206.26 µg/mL.